1996
DOI: 10.1111/j.1365-2222.1996.tb00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased numbers of dendritic cells in the bronchial mucosa of atopic asthmatic patients: downregulation by inhaled corticosteroids

Abstract: Our data suggest that dendritic cells are involved in asthmatic inflammation and that corticosteroids may downregulate the number of dendritic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(37 citation statements)
references
References 36 publications
4
31
1
1
Order By: Relevance
“…In vivo studies also indicate that exposure to glucocorticoids is able to increase the numbers of (suppressor) macrophages (31,33). Our data are in line with such an effect, suggesting that the Mé/DC balance is affected by glucocorticoids, which skew this dynamic equilibrium in a macrophage direction when monocytes are continuously exposed to DEX during DC maturation.…”
Section: Discussionsupporting
confidence: 78%
“…In vivo studies also indicate that exposure to glucocorticoids is able to increase the numbers of (suppressor) macrophages (31,33). Our data are in line with such an effect, suggesting that the Mé/DC balance is affected by glucocorticoids, which skew this dynamic equilibrium in a macrophage direction when monocytes are continuously exposed to DEX during DC maturation.…”
Section: Discussionsupporting
confidence: 78%
“…27 Additionally, an increase in the level of respiratory mucosal DCs that expressed high affinity of IgE receptors has been reported both in allergic rhinitis and asthma conditions. 28 These findings strongly support that DCs have important roles in the pathogenesis and pathophysiology of atopic asthma.…”
Section: Discussionsupporting
confidence: 52%
“…This enriched population of DC precursors provides a readily available source to replenish pulmonary DC, both as part of the normal turnover of these cells and during inflammatory reactions (25,27). In this study, we showed that airway epithelium controls the mobilization of these DC precursors through chemokine secretion.…”
Section: Discussionmentioning
confidence: 67%